The influence of size, clearance, cartilage properties, thickness and hemiarthroplasty on the contact mechanics of the hip joint with biphasic layers() - Li, Junyan (Elsevier Science, 2013)
Computational models of the natural hip joint are needed to examine and optimise tissue sparing interventions where the natural cartilage remains part of the bearing surfaces. Although the importance of interstitial fluid pressurisation in the performance of cartilage has long been recognized, few studies have investigated the time dependent interstitial fluid pressurisation in a three dimensional natural hip joint model. The primary aim of this study was to develop a finite element model of the natural hip incorporating the biphasic cartilage layers that was capable of simulating the joint response over a prolonged physiological loading period. An initial set of sensitivity studies were also undertaken to investigate the influence of hip size, clearance, cartilage properties, thickness and hemiarthroplasty on the contact mechanics of the joint. The contact stress, contact area, fluid pressure and fluid support ratio were calculated and cross-compared between models with different parameters to evaluate their influence. It was found that the model predictions for the period soon after loading were sensitive to the hip size, clearance, cartilage aggregate modulus, thickness and hemiarthroplasty, while the time dependent behaviour over 3000 s was influenced by the hip clearance and cartilage aggregate modulus, permeability, thickness and hemiarthroplasty. The modelling methods developed in this study provide a basic platform for biphasic simulation of the whole hip joint onto which more sophisticated material models or other input parameters could be added in the future.